PENGARUH KOMPENSASI DAN KEPEMIMPINAN TERHADAP MOTIVASI KERJA DAN KAITANNYA DENGAN KINERJA KANTOR XYZ DI KABUPATEN KUBU RAYA - sulasti, Sulasti; Yuliana, Yuliana; Suardi, Suardi; Martono, Martono (STIE 'INDONESIA' Pontianak, 2024)
The purpose of the study is to examine and ascertain how leadership and remuneration affect employee performance and job motivation. Explanatory and associative research methods with saturated samples are used. A Likert scale is used for data measurement, while path analysis is used for data processing. According to test results using standardized variables, leadership has a 23% greater overall influence on performance than other factors. The R2m value of 0.632 was derived from the calculation results. This means that 63.2% of the diversity of data in this research can be explained by the route analysis model, with the remaining 36.8% being explained by mistakes and other variables not included in the model.